Efficacy, immunogenicity and safety of the AS04‐HPV‐16/18 vaccine in Chinese women aged 18‐25 years: End‐of‐study results from a phase II/III, randomised, controlled trial. (15th July 2019) - Zhu, Feng‐Cai; Hu, Shang‐Ying; Hong, Ying; Hu, Yue‐Mei; Zhang, Xun; Zhang, Yi‐Ju; Pan, Qin‐Jing; Zhang, Wen‐Hua; Zhao, Fang‐Hui; Zhang, Cheng‐Fu; Yang, Xiaoping; Yu, Jia‐Xi; et al.
Abstract: Background: Cervical cancer is a major public health concern in China. We report the end‐of‐study results of a phase II/III trial to assess the efficacy, immunogenicity, and safety of the AS04‐human papillomavirus (HPV)‐16/18 vaccine in Chinese women aged 18‐25 years followed for up to 72 months after first vaccination. Results of approximately 57 months following first vaccination have been previously reported. Methods: Healthy 18‐25‐year‐old women (N = 6051) were randomized (1:1) to receive three doses of AS04‐HPV‐16/18 vaccine or Al(OH)3 (control) at Months 0‐1‐6. Vaccine efficacy against HPV‐16/18 infection and cervical intraepithelial neoplasia (CIN), cross‐protective vaccine efficacy against infections and lesions associated with nonvaccine oncogenic HPV types, immunogenicity, and safety were assessed. Efficacy was assessed in the according‐to‐protocol efficacy (ATP‐E) cohort (vaccine N = 2888; control N = 2892), total vaccinated cohort for efficacy (TVC‐E; vaccine N = 2987; control N = 2985) and TVC‐naïve (vaccine N = 1660; control N = 1587). Results: In initially HPV‐16/18 seronegative/DNA‐negative women, vaccine efficacy against HPV‐16/18‐associated CIN grade 2 or worse was 87.3% (95% CI: 5.5, 99.7) in the ATP‐E, 88.7% (95% CI: 18.5, 99.7) in the TVC‐E, and 100% (95% CI: 17.9, 100) in the TVC‐naïve. Cross‐protective efficacy against incident infection with HPV‐31, HPV‐33 and HPV‐45 was 59.6% (95% CI: 39.4, 73.5), 42.7% (95% CI: 15.6, 61.6), and 54.8% (95% CI: 19.3, 75.6), respectively (ATP‐E). At Month 72, >95% of initially seronegative women who received HPV vaccine in the ATP cohort for immunogenicity (N = 664) remained seropositive for anti‐HPV‐16/18 antibodies; anti‐HPV‐16 and anti‐HPV‐18 geometric mean titers were 678.1 EU/mL (95% CI: 552.9, 831.5) and 343.7 EU/mL (95% CI: 291.9, 404.8), respectively. Serious adverse events were infrequent (1.9% vaccine group [N = 3026]; 2.7% control group [N = 3025]). Three and zero women died in the control group and the vaccine group respectively. New onset autoimmune disease was reported in two women in the vaccine group and two in the control group. Conclusions: This is the first large‐scale randomized clinical trial of HPV vaccination in China. High and sustained vaccine efficacy against HPV‐16/18‐associated infection and cervical lesions was demonstrated up to Month 72. The vaccine had an acceptable safety profile. Combined with screening, prophylactic HPV vaccination could potentially reduce the high burden of HPV infection and cervical cancer in China. Trial registration: NCT00779766. Abstract : Cervical cancer is one of the most aggressive forms of cancer that women can suffer from. The presence of human papillomavirus (HPV) is responsible for almost all cases of cervical cancer. For these reasons, the world health organization recommends that HPV vaccines should be included in national vaccination programs. From the first licensure of the first HPV vaccine in 2006 to the development of new HPV vaccines, the latter have been studied in clinical trials and demonstrated to decrease in the number of cervical cancers while remaining acceptably safe. Many developed countries have included HPV vaccination in their program. These countries reported a decrease of cervical cancer cases. Many countries from the less developed regions are still yet to introduce HPV vaccination. The novelty: In 2016, the Chinese authorities approved licensure of the first HPV vaccine for use in China to help prevent cervical cancer and based their decision on clinical trials conducted in China. We present here the final results of the key clinical trial of this HPV vaccine that involved around 6000 Chinese women over 6 years. The impact: Chinese women represent almost 10% of the worldwide population at risk of cervical cancer. Latest estimations from 2016 indicate that 111 000 new cervical cancer cases are reported every year in China. This number could be reduced with the HPV vaccination.